WOMEN IN AFRICA - Falola, Toyin. Link ([S.l.])
1 online resource
Keywords: This book introduces readers to the rich and diverse experiences of women across the African continent, covering their socio-cultural, political, and economic realities from the precolonial era right up to the modern day.In many precolonial African societies, women were empowered and considered to be important participants in the social structures and political systems that managed their communities, but during the colonial era, women were often marginalized. Now, across the continent, women are reasserting their agency. This book explores the various ways in which gender has been constructed in different African cultures across history and how this has impacted the lived experiences of women. The book encompasses a broad range of topics, including history, health, sexualities, gender-based violence, motherhood, education, economic activities, science and technology, religion, popular culture, politics, peacebuilding, feminism, literature, social media, and migration. Engaging and compelling, this book invites us to think again about the changing roles, identities, and contributions of African women across time and space.It is the perfect introduction for any student of gender or African studies, as well as for anyone looking for a reader-friendly guide to the subject.